Traveling-wave antenna model for terahertz radiation from laser-plasma interactions - Jiayu Zhao, Qining Wang, Yuchen Hui, Yamin Chen, Feifan Zhu, Zuanming Jin, Alexander P. Shkurinov, Yan Peng, Yiming Zhu, Songlin Zhuang, Li Lao (SciPost Physics Core, 2022)
Generation of terahertz (THz) wave from air plasma induced by femtosecond laser pulses with a single central frequency (the so-called “single-color”) is one of the fundamental interactions between light and matter, and is also the basis of subsequent pumping schemes using two- or multi-color laser fields. Recently, more states of media beyond gas (e.g., atomic cluster and liquid) via photo-ionization have brought new experimental observations of THz radiation, which can no longer be simply attributed to the mainstream model of the transition-Cherenkov radiation (TCR), thus making the whole picture unclear. Here, we revisited the mechanism of this dynamic process in a new view of the traveling-wave antenna (TWA) model. By successfully reproducing the reported far-field THz radiation profiles from various plasma filament arrangements, the wide applicability of the TWA theory has been revealed. On the other hand in the microscopic view, we investigated the plasma oscillation during filamentation aiming at further bridging the plasma filament and the antenna. Accordingly, THz-plasma resonance has been theoretically and experimentally demonstrated as the elementary THz emitter, paving the way towards fully understanding this important single-color plasma based THz source.